EVALUASI TERHADAP PENGELOLAAN PARKIR TEPI JALAN UMUM DI KAWASAN SIMPANG LIMA KOTA SEMARANG - Syaffa Rahmah; Purwoko .; Dzunuwanus Ghulam Manar (Journal of Politic and Government Studies, 2016)
The research discusses evaluation of management parking in SimpangLima Semarang in order to improve effectiveness of management and receptionarea of parking lot. This research aims to identity implementation of managementof the parking in field with participation identifying roles parties involved andoutlining barriers encountered in the management of parking in area of SimpangLima Semarang.This research uses theories of Government Management according toSamuel e. Overman about application of management functions with new publicmanagement paradigm which mean that public management is interdisciplinarystudy of the general aspects of the Organization and is combination ofmanagement functions such as Planning, Organizing, and ControllingDepartment on one side, with the human resources, financial, physical,informational, and politics on the other. The methods used in this study i.e., mixedmethods, in which qualitative methods are more dominant than quantitative. Thisresearch uses descriptive type of case studies that attempt to describe a symptomin the field. With techniques of data collection in the form of interviews,observation or observation and documentation. Informants in this study wasDishubkominfo, Commission B DPRD Kota Semarang, and implementing asparking at Parking field.It can be inferred that parking policy planning has done well byDishubkominfo where management of the general curb parking in the area ofSimpang Lima refer to Perda No. 1 of 2004 on the Organization of the PublicStreet Parking and Perda No. 2 in 2012 about Retribution. However in themanagement field encountered obstacles in terms of less socializing, givenbehavior of interpreter that parking is not orderly, and existence of barriers tobenefit of the field coordinator who feel have parking lots. Parking managementis ultimately ineffective in the field have an impact on the acceptance of theabsorption area of the parking sector is evidenced by the realizable targetachievement never budget public curbside parking levy.Finally with this research expected street parking managementimprovements to achieve order and local revenue from the parking sector.